The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) VI. Asymmetries and offsets - Perez-Marquez, S (EDP Sciences, 2026)
Context. Asymmetries in debris discs provide unique clues to understand the evolution and architecture of planetary systems. Previous studies of debris discs at (sub)millimetre wavelengths have suggested the presence of asymmetries in a wide variety of systems, yet the lack of sufficiently sensitive high-resolution observations means that the typical properties of debris disc asymmetries have not been studied at the population level. The aim of the ALMA survey to Resolve exoKuiper belt Substructures (ARKS) is to expand our understanding of radial and vertical dust structures, as well as gas distributions and kinematics, in debris discs. The ARKS sample of 24 highly resolved targets in ALMA’s Bands 6 and 7 (1.1–1.4 mm and 0.8–1.1 mm, respectively) provided a unique opportunity to study their asymmetries. Aims. Here, in ARKS VI, we present a systematic analysis of the asymmetries and stellocentric offsets present in the ALMA continuum data for the ARKS survey. Our aims are to (i) identify asymmetries in debris disc dust distributions, (ii) quantify debris disc asymmetry properties, and (iii) discuss the potential origins of debris disc asymmetries. This work is the first systematic analysis of asymmetries in a large sample of well-resolved discs at (sub)millimetre wavelengths. Methods. We utilised empirical methods to identify emission asymmetries (relative to disc major and minor axes, and azimuthal disc locations) and the presence of offset emission between disc centres and the locations of the host stars, via an analysis of their calibration procedures and disc properties. We associated observational asymmetry types (offset, major and/or minor axis, azimuthal) and plausible physical classes (arcs, eccentricities, and possible clumps and warps) associated with each source. Results. We show that there are ten systems, almost half of the ARKS sample, that host either a continuum emission asymmetry or offset emission. Three systems host offsets (HD 15115, HD 32297, and HD 109573 (HR 4796)), four host azimuthal asymmetries (HD 9672 (49 Ceti), HD 92945, HD 107146, and HD 121617), two host an asymmetry in their major axis (HD 10647 (q1 Eri), and HD 39060 (β Pic)), and one hosts an asymmetry in their minor axis (HD 61005). We attribute the offset asymmetries to non-zero eccentricities, and three of the azimuthal asymmetries to arcs. The presence of an asymmetry or offset in the ARKS sample appears to be correlated with the fractional luminosity of cold dust. We tentatively suggest that continuum asymmetries are more prevalent in CO-rich debris discs, suggesting that gas interactions may drive debris dust asymmetries. We identify seven other tentative asymmetries, including four in distinct ARKS systems and three in systems with otherwise significant asymmetries. Conclusions. This study demonstrates that debris disc asymmetries in the ARKS sample are common, and plausibly so in the wider population of debris discs at (sub)-millimetre wavelengths. This means that (sub)-millimetre asymmetries plausibly await discovery in debris discs as we probe these with higher sensitivity and resolution. Throughout, we highlight future studies to further investigate the origins of debris disc asymmetries, and build on the work presented here. © The Authors 2026.